Internet of things. first international summit, IoT360 2014, Rome, Italy, October 27-28, 2014 : revised selected papers /: first international summit, IoT360 2014, Rome, Italy, October 27-28, 2014 : revised selected papers. User-centric IoT : Part I, ([2015]) - Unknown
No abstract available